2007
DOI: 10.1038/sj.npp.1301368
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Blockade or Constitutive Deletion of the Serotonin Transporter Reduces Operant Responding for Food Reward

Abstract: The therapeutic effects of chronic selective serotonin reuptake inhibitors (SSRIs) are well documented, yet the elementary behavioral processes that are affected by such treatment have not been fully investigated. We report here the effects of chronic fluoxetine treatment and genetic deletion of the serotonin transporter (SERT) on food reinforced behavior in three paradigms: the progressive ratio operant task, the concurrent choice operant task, and the Pavlovian-to-Instrumental transfer task. We consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Genetic deletion of the SERT produces a selective 4-to 6-fold elevation in extracellular 5-HT levels (Bengel et al, 1998;Fabre et al, 2000;Shen et al, 2004), providing a selective method of examining how chronically elevated 5-HT contributes to behavior. In the present experiments, responding for the primary reinforcer saccharin was reduced in SERT-KO mice, consistent with findings from Sanders et al (2007) that SERT-KO mice exhibit reduced food-reinforced behavior.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Genetic deletion of the SERT produces a selective 4-to 6-fold elevation in extracellular 5-HT levels (Bengel et al, 1998;Fabre et al, 2000;Shen et al, 2004), providing a selective method of examining how chronically elevated 5-HT contributes to behavior. In the present experiments, responding for the primary reinforcer saccharin was reduced in SERT-KO mice, consistent with findings from Sanders et al (2007) that SERT-KO mice exhibit reduced food-reinforced behavior.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have suggested that SERT-KO mice exhibit reduced rotarod performance and locomotor activity (Holmes et al, 2002;Lira et al, 2003;Morelli et al, 2011). However, as previously suggested by Sanders et al (2007), motor incapacitation is an unlikely explanation for the lower operant response rate in SERT-KO mice. SERT-KO mice made substantially more responses (albeit at reduced level compared with WT controls) for saccharin than for a CRf and a USRf, and their responding for saccharin increased when the schedule of reinforcement was increased from RR2 to RR4 (see Figure 1).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Many experiments support the theory that 5-HT encodes punishment signals by opposing dopamine actions (Tye et al 1977;Hashimoto et al 1996;Clarke et al 2004;Di Giovanni et al 2010;Macoveanu 2014). Altering central 5-HT levels negatively affects reward effects elicited by natural rewarding stimuli Sanders et al 2007), addictive drug (Leccese and Lyness 1984;Smith et al 1986;Carroll et al 1990;McGregor et al 1993;Peltier and Schenk 1993), and electrical ICSS (Redgrave 1978;Bauer et al 2013). Reward inhibition by 5-HT appears to be mainly mediated by the 5-HT2C receptor (Higgins and Fletcher 2003;Cunningham et al 2011;Katsidoni et al 2011).…”
Section: Pharmacological Manipulations Provide Conflicting Viewsmentioning
confidence: 98%
“…For example, knocking out SERT reduces mouse reward-seeking behaviors (Sanders et al 2007) but improves reversal learning (Brigman et al 2010). SERT knockout rats are unable to change behaviors based on expected reward values in a Pavlovian reinforcer devaluation paradigm (Nonkes et al 2010), and respond excessively to the conditioned stimuli in an operant conditioning task (Nonkes and Homberg 2013).…”
Section: Pharmacological Manipulations Provide Conflicting Viewsmentioning
confidence: 99%